Teacher's Strategies for Overcoming Reading and Writing Delays in Lower-Grade Students at SDN 1 Mejobo - Rizki Tsaniazulfa; Sekar Dwi Ardianti; Mohammad Syafruddin Kuryanto (EduBasic Journal: Jurnal Pendidikan Dasar, 2022)
This study aimed to describe the teacher's strategy for overcoming students' reading and writing delays and elucidate the factors influencing lower-grade students' reading and writing delays at SD Negeri 1 Mejobo. This qualitative research was carried out at SDN 1 Mejobo, Mejobo Sub-district, Kudus Regency, taking the subject of teachers and second-grade students. Data collection techniques were performed through interviews, observation, and documentation. The results uncovered that the strategy or learning pattern applied by the teacher in overcoming lower-grade students’ reading and writing delays covered seven stages: 1) identifying students' reading and writing difficulties, 2) ascertaining students who had reading and writing difficulties, 3) consulting learning problems and discussing appropriate strategies to overcome reading delays with fellow teachers, 4) guiding reading together and instructing students to copy readings, 5) inviting students to listen and pay attention to friends who were reading and teaching students to write cursive, 6) dictating texts to students so that they learned to compose sentences and teaching students to make simple essays, and 7) giving assessment and evaluation of students' reading and writing abilities. The effectiveness of the seven stages has been analyzed and could be used as a recommendation for homeroom teachers who want to overcome delays in reading and writing in lower grades. Therefore, it can be concluded that in overcoming reading and writing delays, homeroom teachers have seven strategies that can be utilized as references.